Magnetic resonance tracking of transplanted bone marrow and embryonic stem cells labeled by iron oxide nanoparticles in rat brain and spinal cord - Jendelová, Pavla; Herynek, Vít; Urdzíková, Lucia; Glogarová, Katerina; Kroupová, Jana; Andersson, Benita; Bryja, Vítezslav; Burian, Martin; Hájek, Milan; Syková, Eva (Journal of neuroscience research, 2004)
Nuclear magnetic resonance (MR) imaging provides a noninvasive method for studying the fate of transplanted cells in vivo. We studied, in animals with a cortical photochemical lesion or with a balloon-induced spinal cord compression lesion, the fate of implanted rat bone marrow stromal cells (MSCs) and mouse embryonic stem cells (ESCs) labeled with superparamagnetic iron oxide nanoparticles (Endorem). MSCs were colabeled with bromodeoxyuridine (BrdU), and ESCs were transfected with pEGFP-C1 (eGFP ESCs). Cells were either grafted intracerebrally into the contralateral hemisphere of the adult rat brain or injected intravenously. In vivo MR imaging was used to track their fate; Prussian blue staining and electron microscopy confirmed the presence of iron oxide nanoparticles inside the cells. During the first week postimplantation, grafted cells migrated to the lesion site and populated the border zone of the lesion. Less than 3% of MSCs differentiated into neurons and none into astrocytes; 5% of eGFP ESCs differentiated into neurons, whereas 70% of eGFP ESCs became astrocytes. The implanted cells were visible on MR images as a hypointense area at the injection site, in the corpus callosum and in the lesion. The hypointense signal persisted for more than 50 days. The presence of GFP-positive or BrdU-positive and nanoparticle-labeled cells was confirmed by histological staining. Our study demonstrates that both grafted MSCs and eGFP ESCs labeled with a contrast agent based on iron oxide nanoparticles migrate into the injured CNS. Iron oxide nanoparticles can therefore be used as a marker for the long-term noninvasive MR tracking of implanted stem cells.
Keywords: Stem Cell Transplantation; Animals; Luminescent Proteins; Magnetic Resonance Imaging; Green Fluorescent Proteins; Brain Injuries; Stem Cells; Embryo, Mammalian; Rats, Wistar; Spinal Cord; Microscopy, Electron; komprese míchy; buňky kostní dřeně; železité sloučeniny; Immunohistochemistry; neuroglie; Glial Fibrillary Acidic Protein; transplantace kmenových buněk; poranění mozku; mícha; magnetická rezonanční tomografie; Mice; kmenové buňky; neurony; mozek; kultivované buňky; elektronová mikroskopie; imunohistochemie; transplantace kostní dřeně; myši; zelené fluorescenční proteiny; gliový fibrilární kyselý protein; Cells, Cultured; Neurons; luminescentní proteiny; Brain; Bone Marrow Cells; Neuroglia; Ferric Compounds; krysa rodu Rattus; Bone Marrow Transplantation; zvířata; Phosphopyruvate Hydratase; embryo savčí; Rats; fosfopyruváthydratasa; Spinal Cord Compression; potkani Wistar